2018
DOI: 10.1016/j.hoc.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Key Components of Pain Management for Children and Adults with Sickle Cell Disease

Abstract: Sickle cell disease pain manifests as severe acute pain episodes and a debilitating chronic pain syndrome. Acute pain episodes are the most common reason for health care use; however, acute pain episodes are also frequently managed at home. Chronic pain syndrome develops in 30% to 40% of individuals with sickle cell disease, with an increasing incidence and severity with age. We review the critical aspects of pain management that are integral to the comprehensive approach to sickle cell disease pain and are ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 61 publications
0
43
0
2
Order By: Relevance
“…374 The biology of SCD pain is complex and varied; it likely arises from multiple mechanisms depending on whether an individual is suffering from acute or chronic pain. 375 Pulmonary, 376 orthopedic, 377 psychosocial, 378 and other comorbidities of SCD can also give rise to painful complications in adults and children.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…374 The biology of SCD pain is complex and varied; it likely arises from multiple mechanisms depending on whether an individual is suffering from acute or chronic pain. 375 Pulmonary, 376 orthopedic, 377 psychosocial, 378 and other comorbidities of SCD can also give rise to painful complications in adults and children.…”
Section: Sickle Cell Diseasementioning
confidence: 99%
“…Las crisis agudas de dolor que son de duración variable y se presentan en diferentes sitios del cuerpo, son causadas por una vasooclusión a repetición dispensada gracias a los eritrocitos deformados, lo que resulta en una lesión por reperfusión (en el afán del organismo por restablecer el flujo hacia el sitio afectado por la isquemia); éstas pueden ser desencadenadas por diferentes estímulos como vientos fríos, baja humedad en el ambiente, deshidratación estrés, consumo de alcohol y en mujeres, la menstruación [28,29,30,31]. Por otro lado, el dolor crónico es de carácter larvado y constante pues es desarrollado a partir de la sensibilización paulatina del sistema nervioso [32]. Darbari et al demostraron mediante un estudio llevado a cabo en Escandinavia que los bajos niveles de hemoglobina fetal en adultos están asociados a la magnitud de sensibilización del sistema nervioso central [33].…”
Section: Presentación Clínicaunclassified
“…Frequent acute painful episodes and attendant restrictions on daily activities of life require the combination of judicious opioid administration along with socioemotional supports [5]. Such painful events may be acute or chronic, treated on an inpatient or outpatient basis, or managed with opioid or nonopioid medications [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that up to 30% of adolescents with SCD will ultimately develop chronic pain [9]. The most effective pain management regimens are those that address biological and psychosocial antecedents and consequences of disease manifestations [5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation